(untitled) (Global Journal of Human-Social Science, 2025)
With the rapid advancement of Artificial Intelligence (AI) technology, its application in the field of education has become increasingly widespread. University music classrooms, as a crucial front for music education, are gradually integrating AI technologies to enhance teaching efficiency and optimize learning experiences. However, the application of AI also faces numerous challenges, including the alignment of technology with educational objectives, the transformation of teachers’ roles, cost-related issues, and ethical concerns. From the perspective of instructional design in university music classrooms, this paper systematically explores the specific applications, potential challenges, and future development directions of AI in music education.